Annual mowing maintains plant diversity in threatened temperate grasslands. Issue 2 (15th February 2018) - Smith, Annabel L.; Barrett, Russell L.; Milner, Richard N. C.
Abstract: Questions: Disturbance regimes shaped the evolution of grasslands but grazing exclusion and fire suppression have caused unprecedented increases in grassland biomass and biodiversity declines. Mowing reduces biomass but is not widely practiced in conservation reserves because of concerns about facilitating exotic plant invasion and altering ecosystem function. We asked whether regular mowing affected (1) the diversity of native and exotic functional groups, (2) spatial turnover in vegetation composition (β‐diversity), (3) vegetation attributes relating to biomass and structural heterogeneity, (4) community composition and (5) the distribution and abundance of individual native and exotic species. Location: Five temperate grassland reserves, south‐eastern Australia, encompassing C3 and C4 dominated communities. Methods: Vegetation within reserves had been cut to 10 cm, once per year, for 10 years in late spring/early summer to maintain access tracks. We surveyed plant communities in mowed areas and nearby (<5 m) unmowed control areas (40 subplots per reserve, 200 total) and used linear mixed‐effects models to examine the effects of mowing. Results: Of 24 functional groups, the richness of 16 native and exotic groups significantly increased with mowing. In 14 of these cases, effects were consistent across C3 ‐ and C4 ‐dominated grassland. Mowing reduced spatial turnover, but this did not reduce species richness at any spatial scale. When accounting for species abundance and evenness (Shannon diversity), effects of mowing were generally positive for native species and neutral for exotic species. Mowing increased native perennial grass cover and bare earth, decreased exotic perennial grass cover and litter, and changed community composition. Mowing reduced vegetation height but not structural heterogeneity. Mowing positively affected six individual native species and no exotic species. One native ( Asperula conferta ) and two exotic ( Avena spp. and Nassella neesiana ) species were found in lower abundance on mowed plots. Conclusions: Annual mowing can be a useful conservation tool for threatened temperate grasslands but should be heterogeneous to ensure the persistence of mowing‐sensitive native species. Good vehicle hygiene is essential and localized complementary management (e.g., herbicide) might be required to reduce exotic forbs and grasses. Abstract : Annual mowing, when conducted under a strict vehicle hygiene protocol, had largely positive effects on grassland plant biodiversity and negative effects on exotic invasive species. Mowing can be a practical and affordable way to manage disturbance regimes in grasslands by reducing biomass but should be conducted heterogeneously to ensure the persistence of mowing‐sensitive native species.